2010
DOI: 10.2528/pierm10051203
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Measurement of Complex Permittivity of Composite at Microwave Frequencies Using Scalar Scattering Parameters

Abstract: A shielded, conductor-backed coplanar waveguide technique is used to determine the complex permittivity and loss tangent of nano magnetic composite materials over X-band. The test composite material is synthesized by reinforcing cobalt ferrite particles with average crystallite diameter 7.36 nm in low density polyethylene matrix with 2% and 4% volume fractions. The complex permittivity for low density polyethylene matrix and the composite samples, evaluated from the present technique at 9.887 GHz, are verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In Figure 5 variations of the loss factor with mass filler content at 1 mHz and 1 kHz for 80 o C are presented. For both frequencies, the loss factor values increase with filler content, in accordance with other results obtained for polymer composites with fillers of copper and steel wire [26], iron and nickel-iron powders having the dimensions of 44-149 μm [27], nickel and cobalt ferrite powders [29][30] or nickel particles [31] etc. This is due to the increase of the LDPE/Nd interface area, number of chain ends which are fixed on neodymium particles, and, therefore, the required energy to rotate the polar entities.…”
Section: Loss Factorsupporting
confidence: 88%
“…In Figure 5 variations of the loss factor with mass filler content at 1 mHz and 1 kHz for 80 o C are presented. For both frequencies, the loss factor values increase with filler content, in accordance with other results obtained for polymer composites with fillers of copper and steel wire [26], iron and nickel-iron powders having the dimensions of 44-149 μm [27], nickel and cobalt ferrite powders [29][30] or nickel particles [31] etc. This is due to the increase of the LDPE/Nd interface area, number of chain ends which are fixed on neodymium particles, and, therefore, the required energy to rotate the polar entities.…”
Section: Loss Factorsupporting
confidence: 88%
“…This is because, low saturation magnetization of the substrate makes the insertion loss unaffected for values of µ 0 H 0 > 800 G. In absence of external bias, two notches at 9.91 GHz and 10.05 GHz having insertion loss values −9.871 dB and −7.987 dB, respectively, are observed. The shift in the design frequency from 10 GHz to 9.91 GHz is observed due to uncertainty of 0.5% in the measured complex permittivity values at the design frequency [21]. On increasing the strength of µ 0 H 0 to 400 G along Y -axis of the microstrip line geometry θ = 0 • , it is observed that 9.91 GHz notch does not show much variation in the insertion loss.…”
Section: Microstrip Line Transmission Responsementioning
confidence: 81%
“…The symbols, in (1), have same meaning as mentioned in [18]. The complex permittivity, ε r , and permeability, µ r , of the magnetodielectric substrate material (at the design frequency) are evaluated using shielded conductor backed coplanar waveguide technique [21]. The guided wavelength of the magnetodielectric substrate is determined by substituting the values of (1) and (2) in the equation given below…”
Section: Microstrip Linementioning
confidence: 99%
“…The methods for material property characterizations at microwave frequencies are based on transmission lines and the resonant structures developed from transmission lines [1]. With the development of radar, microwave communication technology and especially the need for antielectromagnetic interference coatings, self-concealing technology and microwave darkrooms the study of electromagnetic wave absorbing materials has increased in recent years [2][3][4].…”
Section: Introductionmentioning
confidence: 99%